Narcissism and Entrepreneurship: A Systematic Review and an Agenda for Future Research - Liu, Dege; Zhu, Ting; Huang, Xiaojun; Wang, Mansi; Huang, Man (Frontiers in Psychology, 2021)
Although narcissism is an important factor influencing entrepreneurial activity and outcomes, not much research has been conducted on the relationship between narcissism and entrepreneurship. To summarize the current literature on this relationship and provide an agenda for further in-depth research, a systematic review was conducted based on the PRISMA guidelines using Web of Science, Elsevier ScienceDirect and EBSCO host databases. Accordingly, thirty-three articles have been identified as being eligible for the final synthesis. The findings of the present study showed, in general, that (1) life history theory, person-environment fit theory and career choice theory were mostly used to explore the topic of narcissism and entrepreneurial intention, social exchange theory was used to analyze narcissistic entrepreneurs’ entrepreneurial motives and attitudes, and upper echelons theory was applied to research on the relationship between narcissism and entrepreneurial outcomes, (2) NPI and narcissistic sub-dimension of the Dark Triad were frequently used self-report scales among 23 identified empirical studies, and (3) narcissism has both bright and dark sides to entrepreneurial activities and outcomes. While narcissism makes potential entrepreneurs have higher entrepreneurial intentions and greater willingness to take risks, it also prevents entrepreneurs from discovering opportunities, acquiring resources and learning from failure. Besides, results also showed that relations between narcissism and entrepreneurial intentions and performance are more complex. For a deeper understanding of this complex relations and advancing research on narcissism and entrepreneurship, more research is necessary to explore the relations between narcissism and entrepreneurship-related variables from a temporal perspective and at the team level, examine the relationship between narcissism and entrepreneurship ethics, and investigate the interaction effects of narcissism and other personalities.